Study on the ways of optimizing the physical training for the sports dance practitioners, juniors 2 category - Roșa Alin Cristian (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2020)
Sports dance is a socio-sports phenomenon that has gained a special spread in recent years, both nationally and worldwide, as evidenced by the growing number of the legitimate athletes, as well as by the intensification of the competitive activity.In this context, the specialists of the field make considerable efforts oriented towards finding the most opportune methods, strategies, means of action in order to obtain the exceptional results that all those who step into a sports dance room want.In this study we aim to develop some strategies for directing and optimizing the physical training of juniors II, by concretely improving the various components of the motor capacity.The research methods used in our approach were the bibliographic study of the literature, the pedagogical observation, the experimental method, the measurement and evaluation methods, the statistical-mathematical method of data processing, the graphical and tabular method.Our experimental approach took place on a sample of 20 subjects (10 girls and 10 boys), aged between 14 and 15, from various sports classes, legitimized at the ACS Top Dance Sports Club 2007, all engaged in the competitive system of the Romanian Federation of the Sports Dance.The statistical analysis of the obtained results revealed thatthere were statistically representativedifferences between the two tests, consequently the used training methodology led to higher indices of motor skills, t-student values validating the research hypothesis.